2016
DOI: 10.1007/s10792-016-0269-5
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the appositions of posterior graft–host junctions with anterior segment optical coherence tomogram after penetrating keratoplasty

Abstract: This study aimed to monitor the graft-host junction's (GHJ's) apposition with anterior segment optical coherence tomogram after penetrating keratoplasty (PK) and correlate the analysis with the preoperative diagnosis. Fifty-one eyes of 50 patients with various preoperative diagnosis of adherent leucoma, pseudophakic bullous keratopathy, corneal opacity or scarring, graft failure, corneal dystrophy and anterior staphyloma, who underwent PK for optical purposes were reviewed retrospectively. Based on the age, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Therefore, AS-OCT has been used to observe alignment patterns of the posterior graft-host junctions after PK. However, similar observations after DALK have rarely been reported [10,11].…”
Section: Introductionmentioning
confidence: 64%
“…Therefore, AS-OCT has been used to observe alignment patterns of the posterior graft-host junctions after PK. However, similar observations after DALK have rarely been reported [10,11].…”
Section: Introductionmentioning
confidence: 64%
“…20 Until now, there have been conflicting opinions about the causes of postoperative astigmatism; these include small intraoperative trephinations, uneven suture tension and graft-recipient misalignments. 8,11 Limberg et al 15 proposed that imprecise graft-host matching might result in astigmatism of about 4 to 6 diopters. 1 Kaiserman et al 11 reported slight misalignment-associated astigmatism after PK.…”
Section: Discussionmentioning
confidence: 99%
“…8,11 Limberg et al 15 proposed that imprecise graft-host matching might result in astigmatism of about 4 to 6 diopters. 1 Kaiserman et al 11 reported slight misalignment-associated astigmatism after PK. Jhanji et al 17 categorized the alignment patterns as step and ledge, but failed to describe the relevance of malappositions to postoperative visual outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Until now, there have been conflicting opinions about the causes of postoperative astigmatism; these include small intraoperative trephinations, uneven suture tension and graft-recipient misalignments. 8,11 Limberg et al 15 proposed that imprecise graft-host matching might result in astigmatism of about 4 to 6 diopters. 1 Kaiserman et al 11 reported slight misalignment-associated astigmatism after PK.…”
Section: Discussionmentioning
confidence: 99%